EP.WE.824Effect of bariatric surgery on gut permeability in humans: a systematic review. (28th October 2021) - O'Brien, James; Robertson, Denise; Griffin, Bruce; Rockall, Timothy; Pring, Chris
Abstract: Aims: Altered intestinal permeability ("leaky gut") is associated with obesity. Several mechanisms have been suggested to explain the harmful sequalae that follow permeability change such as inflammation, alteration to the microbiome and onset of insulin resistance. Studies describe bariatric surgery as having varying effects on intestinal permeability. We aim to summarise and review the literature. Methods: A systematic review was performed using MEDLINE, EMBASE, and Scopus to identify studies in humans that investigated permeability change after bariatric surgery. Results: 5 studies were identified, all cohort. Heterogeneity precluded meta-analysis. All calculated permeability change following oral intake of different sugar solutions. Two studies described a reduction in gastroduodenal permeability post sleeve gastrectomy (SG), one from an increased baseline compared to lean controls. Two described an increase in small intestinal permeability after "malabsorptive" operations (biliopancreatic diversion and duodenal switch). Two found decreased small intestinal permeability at one month post Roux-en-Y gastric bypass and six months post SG. One including only SG had opposite findings of increased small intestinal permeability at 6 months. The only colonic change reported was increased permeability also 6 months post SG. Conclusion: Research found both increased and decreased permeability of the small intestine. Two studies found reduced gastroduodenal permeability post operatively. Evidence regarding the effect of bariatric surgery on the permeability of the gastrointestinal tract and specifically the colon is limited and follow up, operation type and small numbers limit meaningful comparison. Further study into this crucial aspect of obesity both before and after surgery is needed.